Estudo geológico ambiental das Veredas do Rio Formoso no município de Buritizeiro, Minas Gerais - Veridiana Mendes Figueiredo Cristofolo Viana (2006)
In Cerrado there is a ecosystem developed under certain very defined and limited conditions of humidity, which are known as Veredas. In Minas Gerais arid lands, this term is very common in the popular language, meaning river spring or buritizal. This study comprises the Veredas, considered to be important ecological environments embedded in the Sub-bacia in the River of Formoso in Buritizeiro, Minas Gerais. These areas show a recent expansion of the actions made for men, such as monocultivations of Pinus and Eucalyptus, agricultural activities and farming and cattle raising, leading to an uncontrolled exploitation of the natural resources. The perception of the geo-environmental transformations that affect the water supplement directly candy reducing the cycle of life of the trails is evident. This study investigated the socioeconomic, biological and middle physical in the River of Formoso inthe Sub-bacia, and had as objective to establish relations between parameters normalized chemical-fisic and of field, aiming at to the agreement of the origin of this interference in waters of the trails, either antrópica or natural it for the proper rocky basement. The identification of alteration in the chemical parameters followed the values established by the Resolution CONAMA nº. 357/2005, what allowed the verification of actions made for men actions that influence in the original form and possible alterations arising out of these actions in the VEREDAS. This contributes to the development of future environmental researchfocused on the preservation, recuperation and preservation of possible changes in the areas.